2019
DOI: 10.1164/rccm.201806-1095oc
|View full text |Cite
|
Sign up to set email alerts
|

Human Rhinovirus Impairs the Innate Immune Response to Bacteria in Alveolar Macrophages in Chronic Obstructive Pulmonary Disease

Abstract: Rationale: Human rhinovirus (HRV) is a common cause of chronic obstructive pulmonary disease (COPD) exacerbations. Secondary bacterial infection is associated with more severe symptoms and delayed recovery. Alveolar macrophages clear bacteria from the lung and maintain lung homeostasis through cytokine secretion. These processes are defective in COPD. The effect of HRV on macrophage function is unknown. Objectives: To investigate the effect of HRV on phagocytosis and cytokine response to bacteria by alveolar m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 59 publications
2
28
0
1
Order By: Relevance
“…We found that this was not the case, further emphasising that HRV16 specifically affected the internalisation step. These results are important in the context of COPD where HRV is frequently isolated [20] and, together with other defective functions like cell activation [13,[22][23][24], could be one of the explanations as to why patients show bacterial outgrowths post-HRV infection [13,19]. Phagocytosis is strictly dependent on actin polymerisation (for review, Refs.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We found that this was not the case, further emphasising that HRV16 specifically affected the internalisation step. These results are important in the context of COPD where HRV is frequently isolated [20] and, together with other defective functions like cell activation [13,[22][23][24], could be one of the explanations as to why patients show bacterial outgrowths post-HRV infection [13,19]. Phagocytosis is strictly dependent on actin polymerisation (for review, Refs.…”
Section: Discussionmentioning
confidence: 96%
“…However, mounting evidence shows that HRV can infect the lower respiratory tract in patients with chronic inflammatory diseases including chronic obstructive pulmonary disease (COPD) driving disease exacerbations [17][18][19][20]. How HRV disrupts macrophage/monocyte functions remains unknown, but HRV was reported to induce a defective secondary response in macrophages [13,[22][23][24]. How HRV disrupts macrophage/monocyte functions remains unknown, but HRV was reported to induce a defective secondary response in macrophages [13,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, viruses can decrease bacterial clearance contributing to the persistence of bacteria within the airway [ 33 ]. In COPD, rhinovirus specifically has been shown to impair bacterial phagocytosis by macrophages [ 34 ]. Others, using in vitro experiments, have shown alveolar macrophages are less able to mount an immune response to bacteria following HRV infection [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activated B cells utilized mTORC1 to activate p70 ribosomal S6 kinase (p70S6K), and this preceded antibody synthesis(Gaudette et al 2020). In contrast, macrophages that released proinflammatory cytokines played an important role in clearing bacteria, and this was accompanied by the production of nitric oxide (NO) and ROS upon contact with pathogens(Tan et al 2016; Finney et al 2019). Several studies have reported that LXR activation exerted anti-inflammatory functions(Higham et al 2013) and inhibited bacterial infection of host macrophages(Pascual-Garcia et al 2013; Matalonga et al 2017).…”
Section: Discussionmentioning
confidence: 99%